1950
DOI: 10.1085/jgp.33.6.651
|View full text |Cite
|
Sign up to set email alerts
|

Unmedullated Fibers Originating in Dorsal Root Ganglia

Abstract: Information about the physiology of C fibers has been based largely upon studies of visceral nerves; and the properties revealed have, therefore, been those of the unmedullated axons of the postganglionic components of the sympathetic nervous system. An indication that the C fibers in mammafian skin nerves might have properties different from those of their sympathetic analogues first appeared in 1938 (Grundfest and Gasser), when it was observed that the curve of recovery of excitability of C fibers in the sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0
1

Year Published

1952
1952
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(113 citation statements)
references
References 1 publication
6
106
0
1
Order By: Relevance
“…Some of them may be efferent fibres, for according to Heinbecker, O'Leary & Bishop (1933) about 20 % of the non-myelinated fibres in the cat's saphenous nerve are sympathetic motor fibres. These might be the fibres responsible for the smaller C2 elevation, although Gasser (1950) believes that they are not distributed in any single group to give rise to a discrete elevation but contribute to all the elevations of the C potential. Studies on axon reflexes (Coon & Rothman, 1940) have suggested that sympathetic motor fibres in the skin may indeed be excited by ACh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them may be efferent fibres, for according to Heinbecker, O'Leary & Bishop (1933) about 20 % of the non-myelinated fibres in the cat's saphenous nerve are sympathetic motor fibres. These might be the fibres responsible for the smaller C2 elevation, although Gasser (1950) believes that they are not distributed in any single group to give rise to a discrete elevation but contribute to all the elevations of the C potential. Studies on axon reflexes (Coon & Rothman, 1940) have suggested that sympathetic motor fibres in the skin may indeed be excited by ACh.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been suggested that the C2 fibres or many of them may not be sensory at all, but may be sympathetic motor fibres. While the evidence suggests that no more than a small proportion of the nonmyelinated fibres in the saphenous nerve can be specific pain fibres, it must be remembered that C fibres are so numerous in this nerve (according to Gasser (1950) they outnumber all the A fibres several times) that even a small fraction of them would still be a large number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When he cut the sciatic nerve in the dog, at a distance of several centimetres from the dorsal-root ganglion, however, few of the cells died, but again the cells having non-myelinated axons gave evidence of severe axonal reaction (Ranson, 1912). Since physiological differences exist between dorsal-root C-fibres and sympathetic C-fibres (Gasser, 1950), it is safer for the question at hand to rely upon evidence in sympathetic ganglia. Unfortunately, anatomical studies of the axonal reaction in this tissue have been scanty.…”
mentioning
confidence: 99%
“…This was obtained by both stimulating and recording from a posterior root. The distance that we found to be optimal in pilot experiments is about half that which Gasser (1950) found suitable for recording the C action potential in peripheral nerves. A possible reason for the difference is that the diameter of the C fibres of the root central to the ganglion is half that of the fibres peripheral to the ganglion, a fact shown by Gasser (1955); the consequent decrease in conduction velocity would result in greater temporal dispersion over the longer distance.…”
Section: Methodsmentioning
confidence: 91%